Pengaruh Integritas, Independensi dan Kompetensi Auditor Inspektorat Provinsi Sumatera Selatan Dalam Mendeteksi Fraud - Fharadhiba Fharadhiba; Siska Aprianti; Indra Satriawan (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2026)
This study aims to examine the impact of auditor independence, competence, and integrity on the Inspectorate of South Sumatra Province's capacity to identify fraud. In Indonesia, fraud especially corruption is a major issue that causes large financial losses as well as a decline in public confidence. 57 auditors and Regional Government Supervisors (PPUPD) were given questionnaires to complete in order to gather primary data for this study, which employs a quantitative approach using the Explanatory Research technique. Using SPSS version 29 software, multiple linear regression tests and traditional assumption tests were used to analyze the data. The findings indicate that while independence and competence have a favorable and substantial impact on fraud detection, integrity has no discernible effect on these skills. On the other hand, fraud detection capacities are significantly impacted by all three factors (competence, independence, and integrity) at the same time. By enhancing auditor independence and competency, these findings should give the Inspectorate of South Sumatra Province important insights on how to improve internal supervision efficacy.